(untitled) - David E Sadava (Boston, 1993)
This text focused on the biochemistry, molecular biology, and structure of eukaryotic and their organelles. It unfolds in a logical sequence, beginning with a discussion of membranes and then the various membrane-bound organelles. This is followed by the cytoskeleton, nucleur and nucleolus, cell cycle, and ends with the extracellular matrix and cell interactions. The presentation is clear, concise, and up-to-date. It is intended for students who have studied biology and chemistry at the introductory level
Keywords: cell organelles,eukaryotic cells